1980
DOI: 10.1002/jmv.1890050205
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of colostrum and serum immunoglobulins a and g

Abstract: Enteric virus-specific IgA and IgG present in paired human sera and colostrums were measured by the enzyme-linked immunosorbent assay (ELISA). Virus-specific IgA was present in all colostrums, but virus-specific IgG could not be detected. The reverse was true when sera were assayed. Most of these colostrums also neutralized either polio virus or reovirus, as did IgA, which was separated from a pool of colostrums by exclusion chromatography. No correlation could be made between levels of neutralizing and ELISA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Immunoglobulin is present in the blood, tissue fluid, lymph, and external secretions in mammals, and is an important immune factor that has been shown to have many functions, including the prevention of infective agents such as bacteria and viruses from breaching the mucosal barrier, complement activation, counteracting poison, the killing of tumor cells, and disease resistance (Palmer et al, 1980). Glucocorticoids are a class of steroid hormones secreted by the adrenal cortex, which have key roles in regulating the biosynthesis and metabolism of sugars, fats, and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Immunoglobulin is present in the blood, tissue fluid, lymph, and external secretions in mammals, and is an important immune factor that has been shown to have many functions, including the prevention of infective agents such as bacteria and viruses from breaching the mucosal barrier, complement activation, counteracting poison, the killing of tumor cells, and disease resistance (Palmer et al, 1980). Glucocorticoids are a class of steroid hormones secreted by the adrenal cortex, which have key roles in regulating the biosynthesis and metabolism of sugars, fats, and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…CMV IgA antibody in low titer was found in sera of only two seropositive women who had CMV-specific colostrum IgA antibodies. Palmer et al[1980] did not find any enterovirus-specific sera IgA antibody in women with enterovirus-specific colostrum IgA antibody. In previous studies we have shown that the CMV-specific serum IgA appears during primary and recurrent CMV infection [Levy and Sarov, 1980;Sarov, 1980;Sarov et al, 19801.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, colostrum contains lipids (which generate during the digestion process degradation products with anti-infective capacity) and antimicrobial peptides present in casein molecules [79]. Colostrum also contains a collection of immunoglobulins (IgA, IgG and IgM) among which neutralizing antiviral IgA against the poliovirus and the reovirus have been described [80]. Mice fed for 14 days with bovine colostrum and subsequently infected with the human respiratory syncytial virus (hRSV) developed a milder disease with a lower lung titer of the virus with respect to saline fed mice.…”
Section: Colostrummentioning
confidence: 99%